The philosophy of Francisco Suárez - Lagerlund, Henrik; Hill, Benjamin (Colección de libros electrónicos de ULoyola, 2012)
During the seventeenth century Francisco Suárez was considered one of the greatest philosophers of the age. He was the last great Scholastic thinker and profoundly influenced the thought of his contemporaries within both Catholic and Protestant circles. Suárez contributed to all fields of philosophy, from natural law, ethics, and political theory to natural philosophy, the philosophy of mind, and philosophical psychology, and?most importantly?to metaphysics, and natural theology.